Elizabeth Gilbert's Adaptation With Many Cultures In Eat, Pray, Love Movie (2010) By Ryan Murphy: A Sociological Approach - SETIYAWAN, DIDIK (2012)
This study is aimed to show adaptation with many cultures in Eat, Pray, Love movie by using Sociological Approach. The objectives of the study are, to analyze the movie based on the structural elements and describe the movie based on a Sociological Approach. In conducting this study, the researcher uses qualitative research. The data of study is image and text taken from two data sources. The primary source is the Eat, Pray, Love movie itself directed by Ryan Murphy, released in 2010. While the secondary data source are from other materials taken from book, internet and journal which related to the study. The study comes to the following conclusions. First, Ryan Murphy wants to deliver a moral message that is human should be ready to lose everything. The structural elements are related each other and form a unity and. Second, based on the sociological analysis, Ryan Murphy describes that Elizabeth Gilbert is able to adapt well in many cultures with diverse types of adaptation.